Exploring the Diverse Therapeutic Applications of 1, 3-Thiazine: A Comprehensive Review - Agrawal, Neetu; Goyal, Deepika; Pathak, Shilpi (Medicinal Chemistry, 2025)
Thiazine, a six-membered heterocycle containing nitrogen and sulfur atoms, is of paramount importance due to its diverse biological functions and broad therapeutic effects. The pharmacological attributes of 1,3-thiazine span a wide range of activities, including antileukemic, antimycobacterial, anti-inflammatory, sedative, hypnotic, anti-influenza, antituberculosis, melanogenesis inhibition, BACE1 inhibition (with anti-Alzheimer's potential), growth promotion, neuroprotective, and anticonvulsant properties. Consequently, novel synthetic methodologies and the design of new 1,3-thiazine derivatives are significantly influenced by recent research findings. This comprehensive review explores both in vivo and in vitro preclinical studies on the biomedical and therapeutic applications of 1,3-thiazine, highlighting its extensive medical relevance. It is anticipated that derivatization strategies for 1,3-thiazine will open new avenues for the development of innovative biological agents. This review aims to engage researchers, stimulating the creation of promising new treatments and preventive measures for various diseases.
Keywords: heterocycle